PAPARAN LAGU POPULER DEWASA TERHADAP PERKEMBANGAN BAHASA EKSPRESIF PADA ANAK USIA PRASEKOLAH - Ristiyaningsih, Sukma Ayu; Jayadinata, Asep Kurnia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The current development of digital media has influenced people of all ages, including young children, particularly in terms of expressive language development. This study aims to analyze the relationship between exposure to adult-targeted songs and the expressive language development of preschoolers at the Mentari Early Childhood Education Center in Cianjur. The research method employed a quantitative correlational approach. The study subjects included 30 parents of students in Group B and school teachers as respondents. Data collection was conducted in April 2026 using questionnaires and documentation. Data analysis was performed using the Pearson Product-Moment correlation test, followed by the calculation of the coefficient of determination (R²) to determine the percentage of the relationship between the variables. The results of the correlation analysis demonstrated a significant positive relationship between exposure to adult-targeted songs and expressive language development (r = 0.394), with a p-value of 0.031 < 0.05. The coefficient of determination was found to be 15.52%, indicating the extent to which exposure to adult-targeted songs influences expressive language development in this study. The implications of this study are that teachers should utilize songs as a language stimulation strategy, and parents need to be selective in choosing songs appropriate for their children’s developmental age. Further recommendations include using a descriptive qualitative approach to explore vocabulary imitation from adult-targeted songs among preschoolers.